Role Of Supply Chain Management In The Production System Company And Operations - Aji, Ferro (Universitas Stikubank, 2024)
Supply Chain Management is a set of forms for the effective integration of suppliers, manufacturers, warehouses and warehouses, so that goods are produced and distributed in the right quantity, in the right position, at the right time, to minimize costs and provide services to client satisfaction. Currently, many companies are implementing Supply Chain Management to increase the competitiveness of companies with one another. Supply Chain Management is a strategic competitive tool for companies that make competing logical problems a strategy to win the competition. The purpose of making this paper is to explore the budget chain management section in terms of systems and operations within the company that enable it to provide value to consumers in terms of vacuum and speed of service. So that consumers will feel the superiority of the product even though it is physically somewhat similar to other products